Top gun [videorecording (Blu-Ray)] - Cash, Jim; Epps, Jack; Cruise, Tom, 1962-; McGillis, Kelly, 1957-; Kilmer, Val, 1959-; Edwards, Anthony, 1962- (Paramount, 2020)
At the elite Navy Fighter Weapons School, cocky, young pilots compete against one another in the air as well as on the ground. Bonus features include commentary, featurette, music videos, behind-the-scenes, and more.